Human Immunodeficiency Virus Type 2 Capsid Protein Mutagenesis Reveals Amino Acid Residues Important for Virus Particle Assembly. Issue 19 (15th October 2022) - Yang, Huixin; Talledge, Nathaniel; Arndt, William G.; Zhang, Wei; Mansky, Louis M.
Graphical abstract: Highlights: Previous studies revealed differences in HIV-1 and HIV-2 immature particle morphology. A panel of 31 HIV-2 capsid protein site-directed mutants were analyzed. Seven conserved and two non-conserved residues impacted virus assembly. The HIV-2 capsid G38M and N127E mutants had dramatic effects on virus assembly. The 3-fold Gag lattice interface is likely critical for HIV-2 immature particle assembly. Abstract: Human immunodeficiency virus (HIV) Gag drives virus particle assembly. The capsid (CA) domain is critical for Gag multimerization mediated by protein–protein interactions. The Gag protein interaction network defines critical aspects of the retroviral lifecycle at steps such as particle assembly and maturation. Previous studies have demonstrated that the immature particle morphology of HIV-2 is intriguingly distinct relative to that of HIV-1. Based upon this observation, we sought to determine the amino acid residues important for virus assembly that might help explain the differences between HIV-1 and HIV-2. To do this, we conducted site-directed mutagenesis of targeted locations in the HIV-2 CA domain of Gag and analyzed various aspects of virus particle assembly. A panel of 31 site-directed mutants of residues that reside at the HIV-2 CA inter-hexamer interface, intra-hexamer interface and CA inter-domain linker were created and analyzed for their effects on the efficiency of particle production, particle morphology, particle infectivity, Gag subcellular distribution and in vitro protein assembly. Seven conserved residues between HIV-1 and HIV-2 (L19, A41, I152, K153, K157, N194, D196) and two non-conserved residues (G38, N127) were found to significantly impact Gag multimerization and particle assembly. Taken together, these observations complement structural analyses of immature HIV-2 particle morphology and Gag lattice organization as well as provide important comparative insights into the key amino acid residues that can help explain the observed differences between HIV immature particle morphology and its association with virus replication and particle infectivity.